2013
DOI: 10.1007/s00359-013-0829-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ambient humidity on the foraging behavior of the hawkmoth Manduca sexta

Abstract: The foraging decisions of flower-visiting animals are contingent upon the need of an individual to meet both energetic and osmotic demands. Insects can alter their food preferences to prioritize one need over the other, depending on environmental conditions. In this study, preferences in nectar sugar concentrations (0, 12, 24 %) were tested in the hawkmoth Manduca sexta, in response to different levels of ambient humidity (20, 40, 60, and 80 % RH). Moths altered their foraging behavior when placed in low humid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 61 publications
2
52
1
1
Order By: Relevance
“…To overcome thermal extremes and water loss, insects utilize physiological mechanisms such as heat-shock proteins in drosophilid flies (Goto and Kimura 1998;Hoffmann et al 2003;Bubliy et al 2013) and adaptations such as waterproofed cuticles (Bradley 2009). Insects also exhibit behavioural mechanisms such as foraging behaviour to increase consumption of water relative to nutrients (Contreras et al 2013) and relocating to preferred temperature and humidity conditions (Perttunen and Salmi 1956;Heinrich 1993;Tichy 2003). In laboratory studies, Drosophila flies were found to avoid highly saturated environments where relative humidity (RH) exceeded 87% (Perttunen and Salmi 1956), and in a choice test, Drosophila melanogaster Meigen adults clearly favoured air conditions of 3% RH over air saturated at 99% RH (Sayeed and Benzer 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome thermal extremes and water loss, insects utilize physiological mechanisms such as heat-shock proteins in drosophilid flies (Goto and Kimura 1998;Hoffmann et al 2003;Bubliy et al 2013) and adaptations such as waterproofed cuticles (Bradley 2009). Insects also exhibit behavioural mechanisms such as foraging behaviour to increase consumption of water relative to nutrients (Contreras et al 2013) and relocating to preferred temperature and humidity conditions (Perttunen and Salmi 1956;Heinrich 1993;Tichy 2003). In laboratory studies, Drosophila flies were found to avoid highly saturated environments where relative humidity (RH) exceeded 87% (Perttunen and Salmi 1956), and in a choice test, Drosophila melanogaster Meigen adults clearly favoured air conditions of 3% RH over air saturated at 99% RH (Sayeed and Benzer 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that high saturation deficit leads to dehydration and ultimately triggers higher rates of sugar feeding, especially on more dilute sources. Maintaining water balance is essential for insect survival [51, 52] and others have described insect foraging behaviors that balance physiological needs for water and sugar through choice of nectar dilution levels [53-56]. Working with mosquitoes, Hagan et al (2018) found that blood feeding was prompted by dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…High temperatures and low relative humidity levels can severely decrease or alter the nectar sugar concentration, and thereby strongly affect the suitability of the nectar to certain pollinators and thus alter their flower choice (Nicolson , Contreras et al. ). In addition, heat stress might also affect pollen viability and thereby directly reduce plant fitness (Zinn et al.…”
Section: Introductionmentioning
confidence: 99%